Էներգաարդյունավետության վրա մարդկային կապիտալի ազդեցության գնահատումը զարգացող երկրներում - Ադիլխանյան, Հայկ (Bulletin of Yerevan University G: Economics, 2017)
The current study is devoted to the examination and quantification of the influence that human capital exerts on energy sector, in particular on energy efficiency. Emerging countries are studied with a certain emphasis on countries of Commonwealth of Independent States (CIS). Overall, 85 countries are taken for the analysis. As a method of research, panel data analysis is selected. In this context, main panel and panel of CIS countries are estimated. The results reveal that human capital has a significantly positive influence on energy efficiency in case of both panels. Interestingly, for CIS countries that impact is stronger. Besides human capital, positive impact is received for the level of economic development. Conversely, negative effect on energy efficiency is evidenced for the level of industrialization and urbanization, and electricity consumption. For the sample of CIS countries, the impact of urbanization, however, is proved to be insignificant.
Keywords: energy sector, energy efficiency, human capital, panel data analysis, emerging countries, CIS countries